Bioprospecção de fungos endofíticos potencialmente produtores de enzimas lipolíticas aplicáveis na área de alimentos - Elaine Cristina da Costa (2016)
Endophytic fungi from oilseed plants physiologically interact with their host and, therefore, depend on numerous metabolites such as lipolytic enzymes. The esterification reactions between alcohols and organic acids catalyzed by lipolytic enzymes can be used in the manufacture of esters which are used as flavor in foods, beverages, pharmaceuticals and cosmetics. The present work aimed to isolate and select endophytic fungi from baru (Dipteryx alata), cocoa (Theobroma cacao L.), jerivá (Syagrus romanzoffiana) and macaúba (Acrocomia aculeata) seeds, that are potential producers of lipolytic enzymes applicable in the food area. Sixteen endophytic filamentous fungi were isolated from oilseeds, three of them showed hydrolysis halo in selective medium containing olive oil. These fungi were from baru, macaúba and jerivá seeds (B1, M6 and J4) with enzymatic activity index (EAI) 3.82; 1.89 and 1.28, respectively. The isolated fungus from jerivá seed stood out for its lipase activity values (1.2 U.L-1) evaluated by pNPP hydrolysis test and was identified molecularly as Fusarium sp. The lipolytic enzyme produced by this fungus was able to promote the synthesis of butyl acetate and butyl butyrate by esterification (conversion rates of 87.96% and 31.87%, respectively) for 24 h. It was possible to produce this ester with a yield rate of 87.25% in a quarter of the time with 0.9 g of enzyme and 200 mmol.L-1 of acetic acid and butanol, from the optimization of butyl acetate synthesis reaction. The confirmation of synthesized butyl acetate were performed by gas chromatography-mass spectrometry. This work has shown potential use of lipolytic enzymes from Fusarium sp. isolated from jerivá in synthesis of butyl acetate, an ester with pineapple flavor, used in the food industry. Studies of purification, immobilization of this enzyme and its esterification reaction with other substrates may lead to future biotechnology applications of this lipolytic enzyme.